Web-Based Counseling Skills Evaluation Information System Using Design Science Research Methodology (DSRM) Approach - Rangga Gelar Guntara; Muhammad Rizki Nugraha; Muhammad Dzikri Ar Ridlo (Indonesian Scientific Journal, 2023)
This research presents the development of a web-based counseling skills evaluation information system using the Design Science Research Methodology (DSRM) approach. The DSRM approach was utilized to design and develop an effective and efficient information system that meets the requirements of the counseling profession. The research discusses the six stages of DSRM, which include problem identification, solution design, construction, evaluation, communication, and reflection, and how they were used to develop the system. The evaluation stage involved conducting empirical studies to assess the system's effectiveness in supporting counseling skills evaluation. The article concludes that the DSRM approach was effective in developing a web-based counseling skills evaluation information system that meets the needs of the counseling profession. This web using PHP, MySQL and Youtube API. The testing software using blackbox and beta testing. the final results of the study show the level of success of the system in facilitating the process of assessing and evaluating basic counseling skills.